A educação como prática cultural ética: uma leitura possível das propostas de B. F. Skinner - Gianfaldoni, Monica Helena Tieppo Alves (2005)
Ethics and ethic teaching were chosen, because of their importance and nowadays presence, as privileged issues. This work s goal is to present a discussion about ethic that can be described as coming from the radical behaviourism and pointing the educational principles that should be taught, enhancing the dialogue between the two areas. According to the traditional conception, ethics and moral refer to judgements about what is the good, and the acceptable procedures among a specific group; they are historically resulting concepts, products of autonomic, responsible, rational and free men, who act in a conscious and willing way. The skinnerian ethic system, intrinsic product of radical behaviourism and behaviour analyses, does not need of autonomy, rationality and freedom notions in order to propose the existence of three kinds of goods: personal goods, goods the others and goods for the culture, with the survival value as being the foundation of whole system. Skinner warned that part of planet s population does not know about the serious problems that affect us all and the other part which knows it has not taken relevant measures to change them, especially because the major difficulty is that the future always seems to be in conflict with the present. The education, as a control agency, has the privileged role of planning a culture and the educational policy plans, at the end, the Man and the educational practices. The explicit course of action proposals aims for to overcome the obstacles to culture survival producing. The culture adequate planning, let the person be controlled by circumstances, productive actions, it could take care of maximising behaviours with survival values. To transmit the socially produced accumulated knowledge, to produce the behavioural variability, to minimise immediate consequences and maximising the rare ones, to educate to the self-control, to insert the community into values propositions, to use collective criteria to overrule the individual ones, to re-establish the balanced reciprocity, to educate to the productive laze and amusement, to use the face-to-face control and the soft positives reinforcements, to avoid nasty events, to educate to the environment preservation, to teach social and scientific skills, using the technological control it is what could contribute to the consecution of ethic primary value that radical behaviourists should take as an assumption of their behaviours in any situation that face.